1999
DOI: 10.1111/j.1751-0813.1999.tb12092.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐lasting prevention against blowfly strike using the insect growth regulator dicyclanil

Abstract: Under Australian field conditions, a ready-to-use 5% spray-on formulation of dicyclanil applied off-shears or to long wool protected Merino sheep from blowfly strike for a period of at least 20 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 9 publications
3
19
0
Order By: Relevance
“…Studies in Australia using the same dicyclanil formulation showed that the length of protection was approximately the same in Australian Merino sheep treated in long wool or shortly after having been shorn. 11 In the present study all three sites with the highest cumulative strike rate (sites 3, 4, and 5) had relatively short wool (4 to 5 weeks of growth) at the time of product application. Nevertheless, at sites 1, 6, and 8 where the sheep had similar wool length at the time of product application (4 to 6 weeks of growth) the cumulative strike rate was clearly lower.…”
Section: Treatment Strike Probability (%) Riskmentioning
confidence: 43%
See 2 more Smart Citations
“…Studies in Australia using the same dicyclanil formulation showed that the length of protection was approximately the same in Australian Merino sheep treated in long wool or shortly after having been shorn. 11 In the present study all three sites with the highest cumulative strike rate (sites 3, 4, and 5) had relatively short wool (4 to 5 weeks of growth) at the time of product application. Nevertheless, at sites 1, 6, and 8 where the sheep had similar wool length at the time of product application (4 to 6 weeks of growth) the cumulative strike rate was clearly lower.…”
Section: Treatment Strike Probability (%) Riskmentioning
confidence: 43%
“…A length of protection for fine woolled sheep of 19 weeks and beyond is consistent with results obtained using the same dicyclanil formulation on Merino sheep in Australia, where the cumulative strike rate for dicyclanil treated sheep reached 1% around week 20 after treatment, and 2% around week 26 after treatment. 11 Wool length at the time of application varied between four and 24 weeks of growth (Table 1). Studies in Australia using the same dicyclanil formulation showed that the length of protection was approximately the same in Australian Merino sheep treated in long wool or shortly after having been shorn.…”
Section: Treatment Strike Probability (%) Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Insecticides chosen for this treatment have to be relatively long‐acting because of the drawn out nature of the spring emergence, typically from 4 to 7 weeks (Table 2). The availability and ease of application of insect growth regulators to protect sheep against strike for periods of 10–20 weeks are ideal for this purpose (Bowen et al . 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Dicyclanil (ZR ®, ComWin ®), a pyrimidine derivative, is highly active against dipteran larvae and available as a pour-on formulation for blowfly control in sheep in Australia and New Zealand providing up to 20 weeks' protection (Bowen et al, 1999). On the whole, most CSI compouns are very potent against a variety of different pests, especially lepidopterous insects and whiteflies.…”
Section: Dicyclanilmentioning
confidence: 99%